2021
DOI: 10.3389/fphar.2020.531117
|View full text |Cite
|
Sign up to set email alerts
|

Baitouweng Decoction Ameliorates Ulcerative Colitis in Mice Partially Attributed to Regulating Th17/Treg Balance and Restoring Intestinal Epithelial Barrier

Abstract: Ulcerative colitis (UC) is a chronic intestinal disease with unclear pathogenesis. With an increasing global prevalence over the past two decades, UC poses a serious threat to public health. Baitouweng decoction (BTW), a traditional Chinese medicine, has been shown to have good clinical efficacy for treating intestinal inflammation. Yet, the efficacy of BTW in UC and the underlying mechanism remain unclear. The current study aimed to determine whether BTW suppressed intestinal inflammation in mice and the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…The previous studies suggested that the DSS treatment exhibited an increased intestinal permeability, downregulated expression of TJ-related proteins, and impaired subcellular distribution of epithelial TJs . In our study, DSS significantly downregulated TJ-related protein expression, which was consistent with the results of a previous study . However, B. cereus administration significantly upregulated TJ-related protein expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The previous studies suggested that the DSS treatment exhibited an increased intestinal permeability, downregulated expression of TJ-related proteins, and impaired subcellular distribution of epithelial TJs . In our study, DSS significantly downregulated TJ-related protein expression, which was consistent with the results of a previous study . However, B. cereus administration significantly upregulated TJ-related protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…34 In our study, DSS significantly downregulated TJ-related protein expression, which was consistent with the results of a previous study. 35 However, B. cereus administration significantly upregulated TJrelated protein expression. B. cereus was previously reported to enhance the intestinal epithelial barrier function.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, when chronic inflammation is repeatedly irritated, it also quickly progresses to malignant lesions of the colorectal, which poses a threat to the quality of life and life safety of patients [3]. Regarding the pathogenesis of UC, clinical considerations are mainly about colonic mucosal epithelial cells secreting abnormal mucus glycoproteins, changes in the permeability of intestinal mucosal, and antigens entering the intestinal mucosa, leading to a series of inflammatory changes and immune responses, and further production of inflammatory mediators and antibodies, cytokines, and oxygen free radicals, but its ultimate pathogenesis and reasons still need to be further studied [4][5][6]. At present, many scholars tend to believe that it may be related to the autoimmune system, among which, T helper cell 17 ( 17), regulatory T cells (Treg), and cytokines are closely related to their occurrence and recurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its composition mainly includes four herbs: Pulsatilla chinensis , Coptis chinensis , Phellodendron amurense , and Cortex Fraxini [ 88 ]. BTW intervention decreased the expression of cytokines associated with Th17 cells differentiation (including IL-6, IL-1 β , and TNF- α ) and upregulated the expression of IL-10, a key indicator of Treg cells differentiation, thereby regulating the proportion of Th17 cells and Treg cells in mice and restoring Th17/Treg balance, in order to reduce DAI scores and colonic pathological damage in mice [ 89 ]. The ingredients of Jiedu Huayu Decoction (JDHY), a TCM remedy for blood circulation improvement and stasis removal, include Pulsatilla chinensis , Scutellaria barbata , Phellodendron amurense , Portulaca oleracea L., and Coptis chinensis .…”
Section: Chinese Medicine Treatment Strategy Of Balancing Regulation ...mentioning
confidence: 99%